The The Influence Of Customer Satisfaction and Brand Trust on Customer Retention of Telkomsel Prepaid Card Products - Bangun, Loranita; Rezeki, Sri (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This research aims to determine the influence of Customer Satisfaction and Brand Trust on Customer Retention of Telkomsel prepaid card products among visitors to Grapari Graha Merah Putih Medan. This research used a purposive sampling method with 200 respondents using Telkomsel prepaid cards. The data collection technique used was distributing questionnaires whose measurements used an Ordinal scale and were processed statistically using multiple regression analysis and processed with the SPSS 30.0 for Windows program. Data analysis uses the F test and t test for hypothesis testing and multiple linear regression analysis. The research results show that: (1) Customer Satisfaction partially has an influence of 32.4% on Customer Retention, (2) Brand Trust partially has an influence of 38% on Customer Retention and Customer Satisfaction, Brand Trust simultaneously influences Customer Retention. The coefficient of determination (R2) is 0.628, which means that Customer Satisfaction and Brand Trust have an influence of 62.8% on Customer Retention, the remaining 38.2% is influenced by other variables not included in the research.